Transforming Food Systems Under a Changing Climate: Future technologies and food systems innovation for accelerating progress towards the SDGs - key messages - Herrero, Mario; Thornton, Philip K.; Mason-D'Croz, Daniel; Palmer, Jeda (2019)
The global food system is the single largest driver of global environmental change, contributing 24% of greenhouse gas missions, consuming 70% of blue water, and being the primary cause behind the 60% loss of vertebrate biodiversity since the 1970s. In the next three decades we will need a 30-70% increase in food availability to meet the demand for food by an increasingly numerous, urbanised and afuent population. The food system will need to change profoundly if humanity is to be provided with healthy food that is grown sustainably in ways that are both resilient in the face of climate change and do not surpass planetary boundaries. Technological innovation will have a critical role to play in this process. What might be possible if we adopted new, gamechanging technologies in the food system?